Assessment of potential environmental impacts of two large scale irrigation schemes in Ethiopia - Ruffeis, D.; Loiskandl, W.; Spendlingwimmer, R.; Schonerklee-Grasser, M.; Awulachew, Seleshi Bekele; Boelee, Eline; Wallner, K. (2010)
This article presents the findings of a study undertaken to assess environmental impacts of two selected large scale irrigation schemes on natural resources in Ethiopia. The study puts special emphasis on linkages and implications of the utilized water source, ground water hydrology and soil characteristics, on the sustainability of the selected 5chemes. In addition, potential interference of irrigation projects with woodland ecosystems is highlighted. For this purpose primary soil and water data and data from research reports from Wonji/Shoa Sugar Plantation and Finchaa Valley Sugar Estate were collected and analysed using a "before-after" and "with or without" type of analysis. Rising oj groundwater table, water logged within the root zone of the cultivated sugar cane and elevated EC values within 1m of soil depth indicate the? risk of secondary alinization at Wonji/Shoa Sugar Plantation. Unfavourable EC, SAR and RNa values ofthe utilized irrigation source in combination with the CEC ofsoil and ongoing soil erosion processes suggests that irrigation might lead to long-term infiltration problems and destruction of the soil structure at Fincha Sugar Estate. The establishment of the scheme and migration tendencies increased the pressure on the eco-system ofthe valleys and led to clearing of wood and grass lands. To guarantee long-term sustainability, proper study and continuous research of aLready implemented and planned large s.cale irrigation projects is necessary, so that the positive roles of irrigation could be enhanced and timely mitigation measures taken for the negative impacts.